2009
DOI: 10.1039/b918210a
|View full text |Cite
|
Sign up to set email alerts
|

Electron attachment and electron ionization of acetic acid clusters embedded in helium nanodroplets

Abstract: The effect of incident electrons on acetic acid clusters is explored for the first time. The acetic acid clusters are formed inside liquid helium nanodroplets and both cationic and anionic products ejected into the gas phase are detected by mass spectrometry. The cation chemistry (induced by electron ionization at 100 eV) is dominated by production of protonated acetic acid (Ac) clusters, Ac n H + , although some fragmentation is also observed. In the case of anion production (at 2.8 eV electron energy) there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…As mentioned in earlier studies, the position resonances of anions formed inside HNDs are shifted by about 2 eV, mostly due to the conduction band of He [39,45,46]. The parent anions Val − n show two pronounced features at 2 eV and 22 eV as earlier observed for parent anions of DNA bases [39] and other dopants [47][48][49][50]. It is interesting to note that for glycine, alanine and serine the intensity of the parent anions is comparable and sometimes larger than the intensity of the corresponding dehydrogenated cluster anion [50].…”
Section: Anion Formationmentioning
confidence: 50%
See 1 more Smart Citation
“…As mentioned in earlier studies, the position resonances of anions formed inside HNDs are shifted by about 2 eV, mostly due to the conduction band of He [39,45,46]. The parent anions Val − n show two pronounced features at 2 eV and 22 eV as earlier observed for parent anions of DNA bases [39] and other dopants [47][48][49][50]. It is interesting to note that for glycine, alanine and serine the intensity of the parent anions is comparable and sometimes larger than the intensity of the corresponding dehydrogenated cluster anion [50].…”
Section: Anion Formationmentioning
confidence: 50%
“…As observed in earlier studies, we observe a repetition of the resonances after 22 eV which can be explained by an inelastic scattering event of an electron at He, forming He* (which requires an energy of 19.82 eV for the formation of He* in the 2 3 S 1 state) [39,[47][48][49][50][51]. It is interesting to note that at 22 eV all anions are formed, including those that cannot be formed via low-energy electron attachment close to 0 eV.…”
Section: Anion Formationmentioning
confidence: 54%
“…This mass spectrum focuses mainly on the mass region between the dimer and trimer anions, which is also representative of the behavior for higher clusters. As in the case of acetic acid, 27 the yield of the monomer anions of the presently investigated amino acids is more than an order of magnitude lower than the yield of the dimer and trimer cluster anions. Furthermore, the main species observed is the dehydrogenated parent anion, ͓AA-H͔ − , and this is mainly due to gas phase amino acid molecules that leak into the ionization region of the mass spectrometer.…”
Section: A Reaction Productsmentioning
confidence: 99%
“…10 Studies of small cations formed upon ionization of neutral dopants have found evidence of metastable cluster ions, [11][12][13][14][15] but upon electronic or even vibrational excitation of the putatively doped droplets, non-thermal ejection of a free cation from the droplets has been reported. [16][17][18][19][20][21] Spectroscopic analysis has further revealed that for aniline, the helium matrix exerts minimal interference to the line shape and linewidth of the cation in the infrared. 18 More recently, Filsinger et al have embedded hemin + from an electrospray ionization (ESI) source in superfluid helium droplets and reported non-thermal ejection of the dopant upon resonant excitation of the chromophore.…”
Section: Introductionmentioning
confidence: 99%